Improving Student Competence in The Era of The Industrial Revolution 4.0 Through The MBKM Program - Deasy Arisanty; Ersis Warmansyah Abbas; Syahril Syahril; Karunia Puji Hastuti (Social Studies Conference Proceedings, 2022)
Improving Student Competence in The Era of The Industrial Revolution 4.0 Through The MBKM Program